La lettre sur l' « Évangile secret» de Marc et Ie Quis dives salvetur ?: de Clément d' Alexandrie - Le Boulluec, Alain (Apocrypha, 1996)
The long fragment of a letter attributed to Clement of Alexandria dealing with a secret gospel of Mark, which was discovered by Morton Smith in 1958 and edited by him in 1973, is quite controversial. Since the turmoil caused by the oddities of the inventor about the historical Jesus has abated, the NT exegesis gives more and more importance to the indications of the letter to rebuild the synoptical story. Yet no one agrees on the chronological relation between the secret Mark and the canonical Mark. As for the genuineness of the letter, it is not clearly established. Our inquiry is an attempt to find arguments in the comparison between the letter and the Quis dives salvetur ? of Clement, where the latter comments upon Mark 10,17-31. This book is almost certainly posterior to the Stromateis and even to the Hypotyposeis. Moreover it contains a spiritual interpretation of the verses of the gospel. Since the episode by secret Mark is linked with the narrative of Mark 10, 17-31, we may infer, if the letter is Clement's, that the symbolical exegesis of QDS uses parts of secret Mark. The examples we have given here make the hypothesis likely, but not certain.